(untitled) (Inženierzinātņu un augstskolu vēsture, 2018)
2015. gadā atzīmējām ķīmiķa, pedagoga, valsts un sabiedriskā darbinieka Jāņa Celma 120 gadu jubileju, kurš 1935. gadā izveidoja un vadīja Draudzīgā aicinājuma biroju. Bijušā Latvijas Republikas Valsts prezidenta Kārļa Ulmaņa Draudzīgajam aicinājumam atsaucās daudzi kādreizējie Rīgas Politehniskā institūta studenti, tautā saukti par «politehniķiem» – Mārtiņš Bīmanis, Jānis Rapa, Teodors Spāde u. c. Rakstā analizēta J. Celma dzīves darbība, kā arī izvērtēts viņa un citu inženieru ieguldījums Draudzīgā aicinājuma ideju realizēšanā.Chemist Jānis Celms (1895–1968) and his Contribution in Implementation of the Ideas of «Friendly Invitation»In 2015, the 120th birthday of Jānis Celms ‒ chemist, pedagogue, and famous public servant, was celebrated. Eighty years ago, on 28 January 1935, the Prime Minister of Latvia Kārlis Ulmanis invited people of Latvia to participate in the initiative called «Friendly Invitation» encouraging people to donate books, pictures and money to the schools they had attended. The coordination of «Friendly Invitation» lay in the hands of engineer Jānis Celms who began his studies at the Riga Polytechnic Institute and graduated in 1933 from the University of Latvia. While being a student he also worked as a teacher at schools in Riga. The «Friendly Invitation» was well received by people. Former students and alumni of the Riga Polytechnic Institute Mārtiņš Bīmanis, Jānis Rapa, Teodors Spāde and others made significant donations. Jānis Celms went into exile in 1944, first to Germany and then, from 1951, to the USA where he died in 1968. He was decorated with the Order of Lāčplēsis (1926) and the Order of the Three Stars (1936).Keywords: Jānis Celms, Friendly Invitation, Riga Polytechnic Institute.Химик Янис Целмс (1895–1968) и его вклад в реализацию идей «Дружеского призыва»В 2015 году химику, педагогу, государственному и общественному деятелю Янису Целмсу исполнилось 120 лет, а 80 лет назад, 28 января 1935 года, в день своих именин, президент страны Карлис Улманис обратился ко всем латвийцам с «Дружеским призывом». Бюро «Дружеского призыва» создал в 1935 году Я. Целмс, который учился в Рижском политехническом институте и завершил учебу в 1933 году в Латвийском университете. Во время учебы в университете он начинал работать учителем в Рижских школах. На призыв отозвались многие, в том числе бывшие студенты Рижского политехнического института Мартиньш Биманис, Янис Рапа, Теодорс Спаде и др. В 1944 году Я. Целмс с семьей покинул Латвию, жил в Германии, с 1951 года в США до конца жизни в 1968 году. Я. Целмс был награжден Военным орденом Лачплесиса III степени (1926) и Орденом Трех звезд IV степени (1936).Ключевые слова: Янис Целмс, Дружеский призыв, Рижский политехнический институт.